Wetting behaviors of molten melt drops on polycrystalline Al2O3 substrates in high magnetic fields. (15th March 2020) - Liu, Tie; Xiao, Yubao; Lu, Zhengyang; Hirota, Noriyuki; Li, Guojian; Yuan, Shuang; Wang, Qiang
Abstract: We measured the contact angles of Al and Sn drops on polycrystalline Al2 O3 substrates in various high magnetic fields at different temperatures. The contact angles of both Al and Sn drops on the Al2 O3 substrates decreased under high magnetic fields. These decreases strongly depend on the temperature, magnetic flux density, magnetic properties of the metal drops, and the reactivity of the metal drops with Al2 O3 . Our results reveal that the wetting behavior of molten metal drops on ceramics can be modified by a high magnetic field.